The Indicators of Potential Presuppositions in Malala’s Speeches as the Nobel Peace Laureate - Fitriyani, Sefty Hanida; Mujiyanto, Januarius; Warsono, Warsono (English Education Journal, 2021)
Presupposition means that people have their own beliefs before communicating with others (Yule, 1996). He defined the types of presuppositions into six; existential, factive, lexical, structural, counterfactual, and non-factive presuppositions. The study examined the existence of the indicators of potential presuppositions in Malala’s speeches after winning the Nobel and its relation toward the educational field. This study employed a qualitative approach. Four of Malala’s speeches were the data. The researcher used an instrument based on the theory of the indicators of potential presuppositions proposed by Yule (1996). As a result, the researcher found 34 potential presuppositions in Malala’s four speeches; 14 existential, six factual, four lexical, six structural, two non-factive, and two potential counterfactual presuppositions. Being aware of presuppositions will help both students and teachers be good communicators and create a communicative and effective teaching-learning process to achieve the goal. Theoretically, it expounds on the potential presupposition indicators as one of the linguistic expressions by considering the users of those forms in a communication. Pedagogically, it may contribute to the enrichment of educational material. Practically, it could give more ideas and references for further researchers.